Mitochondrial Toxicogenomics for Antiretroviral Management: HIV Post-exposure Prophylaxis in Uninfected Patients - Bañó, Maria; Morén, Constanza; Barroso, Sergio; Juárez, Diana Luz; Guitart-Mampel, Mariona; González-Casacuberta, Ingrid; Canto-Santos, Judith; Lozano, Ester; León, Agathe; Pedrol, Enric; Miró, Òscar; Tobías, Ester; et al. (Frontiers in Genetics, 2020)
Background: Mitochondrial genome has been used in multiple fields as research, diagnosis and toxicogenomics. Several compounds damage mitochondrial DNA (mtDNA), including biological and therapeutic agents, as the human immunodeficiency virus (HIV) and its concomitant antiretroviral treatment. HIV-infected and treated patients may show impaired mitochondrial and metabolic profile. However, specific contribution of treatment or viral toxicity into associated clinical adverse effects remains elusive in HIV and antiretroviral exposed subjects. The evaluation of HIV consequences without treatment interference has been performed in naïve (non-treated) patients, but assessment of treatment toxicity without viral interference is usually restricted to in vitro assays. Objective: The objective of the present study is to determine whether antiretroviral treatment without HIV interference can lead to mtDNA disturbances. We studied mitochondrial and metabolic toxicity in non-infected healthy patients that received HIV post-exposure prophylaxis (PEP) to prevent further infection. We assessed two different PEP schedules according to their composition to ascertain if they were the cause of low adherence, tolerability issues and derived toxicity of PEP regimens. Methods: We analyzed fasting mtDNA from peripheral blood mononuclear cells and metabolic profile before and after 28 days of PEP in 23 patients classified depending on its composition: one protease inhibitor (PI) plus Zidovudine/Lamivudine (PI plus AZT+3TC; n=9) or PI plus Tenofovir/Emtricitabine (PI plus TDF+FTC; n=14). Results: In absence of metabolic disturbances, four-week PEP containing PI plus AZT+3TC led to higher mitochondrial toxicity than PI plus TDF+FTC (-17.9±25.8 vs. 43.2±24.3, p<0.05). MtDNA changes showed a significant and negative correlation with baseline alanine transaminase levels (p<0.05), suggesting the association between mitochondrial toxicity and secondary effects in the hepatic function. Additionally, AZT-containing-regimens showed an increased risk for drug-discontinuation (RR=9.33; CI95%=1.34-65.23). Conclusions: In absence of HIV infection, preventive short antiretroviral treatment can cause subclinical mitochondrial damage, especially pyrimidine-analogues as AZT, that still rank as the alternative option and first choice in certain cohorts for PEP. Coming efforts should be focused in launching new strategies with safer mitochondrial and toxic profile. PEP-treated patients convey an outstanding opportunity to assess antiretroviral toxicity in vivo, where mtDNA is confirmed as the gold standard for mitochondrial toxicogenomics in antiretroviral management.